Glosa do wyroku Trybunału Konstytucyjnego z dnia 4 lipca 2023 r., sygn. akt SK 14/21 - Warston, Anna (PRAWO i WIĘŹ, 2025)
The subject of the judgment under review is the issue of the application of the reference to the definition of a structure contained in the Local Taxes and Fees Act, and thus the violation of the principles of certainty and definiteness of tax law. Such a move on the part of the legislator arouses numerous controversies, since in the Court’s opinion it is not permissible to regulate in a non-tax law such essential elements of the legal construction of a tax as its subject matter. This paper also considers whether the Constitutional Court’s rationale can be the basis for the tax authorities’ failure to comply with the Constitution. The author points out the negative effects of the regulation, as well as the relevance of the Constitutional Court’s position to the existence of the tax obligation of citizens.